Development of capabilities from the innovation of the perspective of poverty and disability - José Luis Sánchez García; Sergio Pérez Ruiz (Journal of Innovation & Knowledge (JIK), 2017)
Poverty is a reality that is present to a greater or lesser extent in all regions of the world. Disability, like poverty, is also a reality in the society in which we live. Disability is not only a reality, but an inescapable truth, as at some point in life all people will be vulnerable and will exhibit some form of disability. When combined, poverty and disability immerse a person in more serious circumstances. Within the concept of poverty, disability means greater poverty. Based on a correct conceptualization of what poverty and disability are, this paper aims at proposing an innovative model of accompaniment, one which starts from a complete and multidimensional vision of reality, where the focus is on the human person, understood as a radical novelty, and characterized by singularity and uniqueness. The model presented herein addresses issues that affect both the person being accompanied and the person providing help. The main idea in this model is the development of capabilities in the person with disability and in the person providing the help.
Keywords: A13; F0; I1; Z1; 650; Poverty; Disability; Vulnerability; Person; Accompaniment